The nature of disappearing : a novel - Grant, Kimi Cunningham (Minotaur Books, 2024)
"Emlyn doesn't let herself think about the past. How she and her best friend, Janessa, barely speak anymore. How Tyler, the love of her life, left her half dead on the side of the road three years ago. Her new life is simple and safe. She lives alone in her Airstream trailer and works as a fishing and hunting guide in scenic Idaho. Her closest friends are the community's makeshift reverend and a handsome Forest Service ranger who took her in at her lowest. But when Tyler shows up with the news that Janessa is missing, Emlyn is propelled back into the world she worked so hard to forget. Janessa has become a social media star, documenting her #vanlife adventures with her rugged boyfriend. She hasn't posted lately, though, and when Emlyn realizes the most recent photo doesn't match up with its caption, she reluctantly teams up with Tyler to find her old friend. As the two trace Janessa's path through miles of wild country, Emlyn can't deny the chemistry still crackling between them. But the deeper they press into the wilderness, the more she begins to suspect that a darker truth lies in the woods--and that Janessa isn't the only one in danger."--